1993
DOI: 10.1037/0012-1649.29.4.611
|View full text |Cite
|
Sign up to set email alerts
|

Friendship and friendship quality in middle childhood: Links with peer group acceptance and feelings of loneliness and social dissatisfaction.

Abstract: The impact of after-school peer contact on early adolescent externalizing problems is moderated by parental monitoring, perceived neighborhood safety, and prior adjustment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

109
1,691
13
144

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 1,678 publications
(2,002 citation statements)
references
References 40 publications
109
1,691
13
144
Order By: Relevance
“…Like prior research onrejected children (Parker & Asher, 1993), findings in the present study demonstrated that the best friendships of shy and socially withdrawn children were qualitatively poorer than the best friendships of children who were not removed from the peer group at-large. As expected, shy/withdrawn children rated their best friendships as significantly lower in help and guidance, intimate disclosure, conflict resolution, and overall friendship quality than did control children.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Like prior research onrejected children (Parker & Asher, 1993), findings in the present study demonstrated that the best friendships of shy and socially withdrawn children were qualitatively poorer than the best friendships of children who were not removed from the peer group at-large. As expected, shy/withdrawn children rated their best friendships as significantly lower in help and guidance, intimate disclosure, conflict resolution, and overall friendship quality than did control children.…”
Section: Discussionsupporting
confidence: 77%
“…Children were considered "best friends" if they were each other's very best or second best friend choice. The identification of a best friendship is similar to procedures used in other studies focused on best friendships (e.g., Parker & Asher, 1993). Although children could nominate any samegender child in their grade as their best friend, only participating children completed the friendship nominations; therefore, it was impossible to determine whether a friendship was reciprocated when a nonparticipating child was identified as a best friend.…”
Section: School Measuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Peer relationship theorists distinguish between competencies required for dyadic friendship and group-level acceptance (e.g., Bukowski & Hoza, 1989;Parker & Asher, 1993). For instance, in later childhood, the skills necessary for high-quality friendships include demonstrating loyalty, trust and engaging in appropriate self-disclosure; whereas those required for peer acceptance include adherence to peer norms for behavior, appearance, and activities.…”
Section: Multilevel Early Childhood Moderators Of Anxious Solitary Chmentioning
confidence: 99%